Vocal repertoire for the twenty-first century, Volume 1: Works written before 2000 - Manning, Jane 1938-2021 (Oxford scholarship online, 2020)
An insightful and practical interpretive guide to contemporary repertoire assembled by celebrated soprano Jane Manning. This first volume of the two-volume set covers works composed prior to the year 2000